Mechanisms for controlling Dorsal nuclear levels - McGehee, James; Stathopoulos, Angelike (Frontiers in Cell and Developmental Biology, 2024)
Formation of the Dorsal nuclear-cytoplasmic gradient is important for the proper establishment of gene expression patterns along the dorsal-ventral (DV) axis during embryogenesis in Drosophila melanogaster. Correct patterning of the DV axis leads to formation of the presumptive mesoderm, neurogenic ectoderm, dorsal ectoderm, and amnioserosa, which are tissues necessary for embryo viability. While Toll signaling is necessary for Dorsal gradient formation, a gradient still forms in the absence of Toll, suggesting there are additional mechanisms required to achieve correct nuclear Dorsal levels. Potential mechanisms include post-translational modification, shuttling, and nuclear spacing. Post-translational modification could affect import and export rates either directly through modification of a nuclear localization sequence or nuclear export sequence, or indirectly by affecting interactions with binding partners that alter import and export rates.Shuttling, which refers to the facilitated diffusion of Dorsal through its interaction with its cytoplasmic inhibitor Cactus, could regulate nuclear levels by delivering more Dorsal ventrally.Finally, nuclear spacing could result in higher nuclear levels by leaving fewer nuclei in the ventral domain to uptake Dorsal. This review details how each of these mechanisms may help establish Dorsal nuclear levels in the early fly embryo, which serves as a paradigm for understanding how the dynamics of graded inputs can influence patterning and target gene expression. In addition, careful analysis of nuclear Dorsal levels is likely to provide general insights as recent studies have suggested that the regulation of nuclear import affects the timing of gene expression at the maternal-to-zygotic transition.